Catur Murti Counseling in Improving University Students’ Self-Esteem - Miftahul Djanah; Bakhrudin Habsy; Syarifatul Aini; Siti Arifah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
This study examined the effectiveness of Catur Murti Counseling in improving self-esteem among university students. The researcher employed a quantitative method with a pre-experimental design, specifically the one-shot case study. The researcher used the Rosenberg Self-Esteem Scale (RSES) as the data collection instrument. This instrument demonstrated item-total validity with R values above 0.32 and a reliability coefficient of 0.983, indicating that the self-esteem inventory is reliable and suitable for research purposes. The researcher analyzed the data using the non-parametric Two Independent Sample Test: Mann-Whitney U. The hypothesis testing yielded a Z value of -2.242 and an Asymp. Sig. (2-tailed) value of 0.025 (< 0.05), which led to the rejection of Ho. This result indicates that cognitive behavioral group counseling effectively improves students' self-esteem. Furthermore, the paired-samples t-test analysis yielded a t-value of -11.534 and a p-value of 0.000. Since 0.000 < 0.05, the researcher accepted Ha, confirming that Catur Murti Counseling effectively enhances university students’ self-esteem. Counseling practitioners and teachers are expected to pay attention to Catur Murti Counseling, which is scientific and practical in addressing various problems, especially those related to university students' self-esteem. Keywords: catur murti counseling; self-esteem; mental health; university students; quality education; good health and wellbeing